Synthesis and analysis of SnO2/ZnO nanocomposites: Structural studies and optical investigations with Maxwell–Garnett model - Benali, M.A.; Tabet Derraz, H.; Ameri, Ibrahim; Bourguig, A.; Neffah, A.; Miloua, Redouane; Yahiaoui, I.E.; Ameri, Mohammed; Al-Douri, Yarub (Elsevier, 2020)
SnO2 including different concentrations of ZnO has synthesized using spray pyrolysis technique for preparing on glass substrate at 350 °C. Effect of ZnO ratio has been researched to study optical and structural properties of SnO2. X-ray diffraction scheme indicates the presence of different peaks that attribute to a mixture of rutile SnO2 and hexagonal ZnO. The crystallite size of SnO2 decreases as ZnO ratio increases. The synthesized nanocomposites are characterized via field emission-scanning electron microscopy. The reflectance and transmittance in the wavelength range, 200–2500 nm have been measured. The direct band gaps vary from 3.04 to 3.78 eV to show contrary concept to Ubach's energy. The refractive index and extinction coefficient display vibrations due to ZnO ratio effect. Dielectric constants of SnO2 are deduced effectively in terms of ZnO ratio using Maxwell-Garnett ‘s effective medium theory, they are compared with experimental spectra. The optical properties can be interpreted correctly with Maxwell-Garnett theory of small underestimation, indicating that adaptation of optical properties can take place by varying the volume fraction. Our results present good agreement with experimental data. © 2019 Elsevier B.V.